Do Individual and Economic Perceptions Affect Agropreneurship Intentions? - Heptari Elita Dewi (Jambura Agribusiness Journal, 2025)
The declining participation of younger generations in agriculture has intensified concerns regarding agricultural regeneration and the future supply of agripreneurs. Although economic incentives are frequently assumed to motivate young people to enter agricultural entrepreneurship, less is known about whether economic considerations outweigh individual perceptions in shaping Agropreneurship intentions. This study investigates the relative roles of individual and economic perceptions in predicting Agropreneurship intentions among 669 first-year students enrolled in Agribusiness, Agroecotechnology, and Forestry programs at an Indonesian university. Data collected through a structured questionnaire were analyzed using partial least squares structural equation modeling (PLS-SEM). The results reveal that individual perceptions have a positive and significant association with agropreneurial intention (β = 0.417, p 0.001) and demonstrate a moderate effect size (f² = 0.164). Economic perceptions are also positively associated with Agropreneurship intentions (β = 0.169, p 0.001); however, their effect is substantially smaller (f² = 0.027). The model explains 28.2% of the variance in Agropreneurship intentions and exhibits predictive relevance (Q²predict = 0.272). These findings challenge an exclusively economic interpretation of young people's willingness to pursue agricultural entrepreneurship by showing that individual perceptions are considerably more influential than perceived economic benefits. The study suggests that agricultural universities and entrepreneurship programs should complement information about profitability and employment opportunities with interventions that strengthen students' confidence, perceived capability, exposure to entrepreneurial role models, and acceptance of agriculture as a viable career. The findings provide empirical insights for designing youth agropreneurship development strategies in emerging agricultural economies.